1998
DOI: 10.1111/j.1469-7793.1998.831bd.x
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of pH‐dependent mechanisms to fatigue at different intensities in mammalian single muscle fibres

Abstract: The contribution of intracellular pH (pHi) to the failure of Ca2+ release and inhibition of contractile proteins observed during fatigue was assessed in single intact mouse muscle fibres at 22 °C. Fatigue was induced by repeated tetani at intensities designed to induce different levels of intracellular acidosis. Force and either intracellular free Ca2+ concentration ([Ca2+]i; measured using indo‐1) or pHi (measured using SNARF‐1) were recorded in fibres fatigued at two different intensities. Intensity was vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(92 citation statements)
references
References 38 publications
(73 reference statements)
3
83
1
4
Order By: Relevance
“…In addition, some studies have indicated that high H + concentrations can inhibit the linking of Ca +2 to troponin and thereby inhibit the interaction between contractile proteins. 10 Dose and treatment procedure seem to be important to achieve positive effects of LLLT in muscle tissue. In previous studies we had irradiated the biceps muscle at 4 locations using a single-diode laser but failed to find significant differences in blood lactate levels compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies have indicated that high H + concentrations can inhibit the linking of Ca +2 to troponin and thereby inhibit the interaction between contractile proteins. 10 Dose and treatment procedure seem to be important to achieve positive effects of LLLT in muscle tissue. In previous studies we had irradiated the biceps muscle at 4 locations using a single-diode laser but failed to find significant differences in blood lactate levels compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…However, this acidosis is not an invariable accompaniment of muscle activity and presumably depends on the extent to which anaerobic glycolysis is switched on and the rate at which protons leave the muscle on the lactate transporter or the Na ϩ /H ϩ exchanger. Typically after long-lasting activity, particularly at a low duty cycle, there is little or no acidosis (91,452) (see sect. VIIB).…”
Section: Metabolic Changes In Working Musclesmentioning
confidence: 99%
“…Many studies on muscle fatigue using mechanically dissected single FDB fibers have been carried out at room temperature (15)(16)(17). In one study carried out at 37°C (37), tetanic contractions were 400 ms long, and under those conditions, fibers stopped contracting within 1.5 s because of a large ROS production.…”
Section: Membrane Excitability and Contractile Characteristicsmentioning
confidence: 99%